2016
DOI: 10.1177/1708538115612637
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacomechanical thrombolysis with a rotator thrombolysis device in iliofemoral deep venous thrombosis

Abstract: New thrombolytic devices seem to reduce in-hospital mortality risks and may potentially decrease post-thrombotic morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The mean follow-up time was 12.3 months (range, 1-82 months). Four different categories of thrombectomy devices were used among the included studies: rheolytic devices, [6][7][8][9][10][11] aspiration devices, [12][13][14][15][16] rotational devices, [16][17][18][19][20][21] and ultrasound-enhanced thrombolysis devices. 14 They aimed to achieve transcatheter removal of thrombi via different mechanical means.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow-up time was 12.3 months (range, 1-82 months). Four different categories of thrombectomy devices were used among the included studies: rheolytic devices, [6][7][8][9][10][11] aspiration devices, [12][13][14][15][16] rotational devices, [16][17][18][19][20][21] and ultrasound-enhanced thrombolysis devices. 14 They aimed to achieve transcatheter removal of thrombi via different mechanical means.…”
Section: Resultsmentioning
confidence: 99%
“…A study described pharmacomechanical thrombolysis with a rotator thrombolysis device in iliofemoral deep venous thrombosis in 67 patients. 18 Immediate total recanalization was conducted in all patients, the leg diameters returned to normal ranges in the early postoperative period, and hospital mortality or severe complications were not detected. In general, the ACCP guidelines recommend anticoagulant alone over thrombolysis or catheter-assisted thrombus removal including in patients with acute DVT and PE.…”
Section: Management Of Proximal Dvt and Symptomatic Pementioning
confidence: 90%
“…Early thrombus removal has been advocated to prevent PTS providing venous tract open and healthy venous valve competence 9 . Several studies have shown that CDT with or without an additional procedure such as US-accelerated, pharmacomechanic-assisted intervention is effective to obtain a dramatic reduction in the PTS incidence 6,7,10,11 . However, in their study, Kim et al 12 reported that CDT was unable to prevent PTS and its efficacy was controversial.…”
Section: Discussionmentioning
confidence: 99%